The effect of temperature change on metabolism: separating biological and chemical reactions - Rychert, Krzysztof (Ecological Questions, 2022)
Life-detection experiments carried out in extraterrestrial locations provided inconclusive results whether processes observed were biological or chemical. In this study, the typical effect of temperature on metabolic rates is described and a life-detection method that is easy to perform is proposed. The method comprises observing changes in microbial metabolic rates after temperature shift. The method was demonstrated by experiments on aquatic microorganisms in the Gulf of Gdansk (Baltic Sea). First experiment, in which temperature was shifted within the temperature range encountered at the sampling site, demonstrated a typical Q10 coefficient (2.84). The experiment in which temperature was shifted beyond the environmental temperature range provided an unexpectedly low Q10 coefficient (1.44), which indicated that excessive temperature exerted an inhibitory effect on metabolism. This response is not expected for chemical reactions, but it is typical for biological processes. In summary, a pair of properly-tailored experiments permitted separating biological and chemical reactions.